Nisin and ε-poly-L-lysine as natural antimicrobials towards spoilage-associated Lactobacillus plantarum - Fernanda Cristina Kandalski Bortolotto; Maria Helena da Rosa Farfan; Nathalia Cristina Kleinke Jede; Gabriela Maia Danielski; Renata Ernlund Freitas de Macedo (Ciência Rural, 2020)
ABSTRACT: Sausages are highly susceptible to microbial spoilage. Lactic acid bacteria (LAB) is the main group of spoilage bacteria in vacuum packed cooked sausages. To control microbial growth natural antimicrobials have been used as food preservatives. The aim of this study was to identify strains of lactic acid bacteria isolated from spoiled commercial Calabresa sausages and use them in an in vitro challenge with the natural antimicrobials, nisin (NI) and ε-poly-L-lysine (ε-PL). Mass spectrometry identification of LAB isolated from sausages using MALDI-TOF revealed a predominance of L. plantarum in the LAB population. RAPD-PCR of L. plantarum strains showed four different genetic profiles. Minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of NI and ε-PL, alone and in combination, against a pool of different profiles L. plantarum were determined. MIC of NI and ε-PL were 0.468 mg/ L and 75 mg/ L; respectively, whereas MBC of NI and ε-PL were 12.48 mg/L and 150 mg/L, respectively. The combined effect of NI and ε-PL was determined using concentrations at 1/4 and 1/8 of individual MICs. Synergistic effect was confirmed at both concentrations showing a fractional inhibitory concentration index of 0.5 and 0.2, respectively. The combination of NI and ε-PL at a small concentration of 0.05 mg/L and 9.375 mg/L, respectively, showed inhibitory effect towards spoilage L. plantarum Results show the potential of the combined use of NI and ε-PL to control sausage spoilage-associated with lactobacilli.